Mitochondrial DNA mutations in papuan humans: characterization of whole genome sequences and its application for susceptibility to disease - YOHANIS NGILI,; ROSYE H.R. TANJUNG, (International Journal of Pharma and Bio Sciences, 2019)
The importance of mitochondrial genome (mtG) as the site of disease-related mutations has become apparent in the last few years, and recent developments have started to reveal the molecular genetics and pathology of these disorders, leading to recognition of the major role that mtG mutations play in disease and the aging process. The mutations that occur in mtG could also increase intracellular ROS production, so that the production of free radicals decreases mitochondrial function and will increase oxidation stress in various tissues. Pathogenic mutations generally occur in the form of heteroplasmi, which is the ratio of the number of mutant mtDNA to wild type mtDNA that varies in each tissue, with low levels of heteroplasmi in blood cells (leukocytes) and high in postmenocytic tissue. The results of the mutation analysis showed the presence of point mutations in almost all fragments of the mtG region with different proportions. The ATP6 gene segment located in the 8000s area can be selected for studies in forensic medicine and bioetnoanthropology studies. Another thing to note is that the preparation and development of human mtG nucleotide variation databases which can be a good reference to facilitate research on variations in mutations that are normal and that cause disease in humans.